2014
DOI: 10.1111/fog.12057
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns ofPacific halibut (Hippoglossus stenolepis) in relation to environmental variables along the continental shelf waters of theUS WestCoast and southernBritishColumbia

Abstract: Knowing how Pacific halibut (Hippoglossus stenolepis) distribute in relation to ocean conditions is of primary importance to halibut managers, as they are tasked with estimating stock size and designing effective monitoring programs amidst a changing climate. This research examined near‐bottom environmental data alongside halibut survey catch data for the years 2006–2009 on the continental shelf of Oregon, Washington, and southern British Columbia. The objectives of the research were to: (1) characterize summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
(89 reference statements)
3
17
0
Order By: Relevance
“…Observed range changes in non-hypoxia tolerant halibut, adds weight to the findings of AR5 (Sadorus et al, 2014). The work of Cheung et al (2014) supports the assertions of the AR5, finding high sensitivity in the larvae of benthic invertebrates.…”
Section: Updates To Ar5supporting
confidence: 60%
“…Observed range changes in non-hypoxia tolerant halibut, adds weight to the findings of AR5 (Sadorus et al, 2014). The work of Cheung et al (2014) supports the assertions of the AR5, finding high sensitivity in the larvae of benthic invertebrates.…”
Section: Updates To Ar5supporting
confidence: 60%
“…Sadorus et al. () found a significant relationship between dissolved oxygen and catch rates of Pacific halibut. Primary production (plankton) concentration and distribution and subsequent changes in secondary production levels have also been linked to groundfish abundance (Francis et al., ; McGowan, Cayan, & Dorman, ).…”
Section: Discussionmentioning
confidence: 99%
“…SST may also be a proxy for other environmental variables, such as oxygen levels, ocean mixing, and plankton availability, that may affect these groundfish to varying degrees. Sadorus et al (2014) found a significant relationship between dissolved oxygen and catch rates of Pacific halibut. Primary production (plankton) concentration and distribution and subsequent changes in secondary production levels have also been linked to groundfish abundance (Francis et al, 1998;McGowan, Cayan, & Dorman, 1998 Notes.…”
Section: Control Of Bayesian Parameter ϕ In Crossvalidationmentioning
confidence: 91%
See 1 more Smart Citation
“…Ocean warming as a result of climate change, sometimes in combination with other drivers, can affect the distribution, abundance, species richness, and ecology of many of the organisms-both hosts and parasites-living in the oceans (Kaschner et al, 2011;Marcogliese, 2008;Sadorus et al, 2014). Of particular concern for foodborne parasites are the various vertebrates and invertebrates consumed by people.…”
Section: Direct Effects Of Climate Change During Productionmentioning
confidence: 99%